Parents' perceptions of disclosure of the diagnosis of cerebral palsy. Issue 6 (1st December 2000) - Baird, G; McConachie, H; Scrutton, D
Abstract : The aim of the paper is to propose guidelines for good practice in disclosing the diagnosis of cerebral palsy to parents. The guidelines draw on an interview study with parents of 107 children, average age 24 months, in the South East Thames region. In addition case notes were examined, and mothers completed questionnaires to measure current levels of depression and coping strategies. Dissatisfaction with how the diagnosis had been disclosed was greater where children had been premature and/or low birth weight, where they developed more severe degrees of physical disability, and where the diagnosis had been made later. Dissatisfaction was related to greater degrees of later self reported depression. The guidelines take account of the findings, in particular the need for early close liaison between neonatology and community paediatric services. Suggestions are made for how to ensure implementation and monitoring of good practice.